2007
DOI: 10.1142/s0192415x07005144
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Pharmacological Preconditioning of Total Flavones of Abelmoschl Manihot on Cerebral Ischemic Reperfusion Injury in Rats

Abstract: The present study was to investigate the effect of pharmacological preconditioning of total flavones of Abelmoschl Manihot (TFA) on cerebral ischemic reperfusion injury in rats. Rat cerebral ischemia/reperfusion injury was induced by occluding the right middle cerebral artery (MCA). The infarct size was determined by staining with 2,3,5-triphenyl tetrazalium chloride (TTC). The serum malonaldehyde (MDA), nitric oxide (NO) and lactate dehydrogenase (LDH) levels were measured by using spectrophotometry; Inducibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Abelmoschus manihot flavonoids were also proved to be effective for protecting poststroke depression injury in mice (Liu et al, 2009) and cerebral ischemic reperfusion injury in rats (Wen & Chen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Abelmoschus manihot flavonoids were also proved to be effective for protecting poststroke depression injury in mice (Liu et al, 2009) and cerebral ischemic reperfusion injury in rats (Wen & Chen, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…15,22 TFA has been found to have therapeutic effect on cerebral ischemic reperfusion injury and poststroke depression in the corresponding animal models. 13,23 The chemical constituents of TFA have been isolated, and their structures have been identified by spectroscopic analysis. TFA contains seven flavone glycosides that were identified as quercetin-3-O-robinobioside, hyperoside, isoquercetin, hibifolin, myricetin, quercetin-3 0 -O-glucoside, and quercetin.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 As a well-known traditional Chinese medicine, Flos Abelmoschus manihot L. Medic has been used as the neuroprotective drug for cerebral ischemic reperfusion injury in recent studies. 13,14 Total flavone glycosides of Flos A. manihot (TFA) contain seven chemically identified flavone glycosides 15 and have therapeutic effects on cerebral ischemic reperfusion and postmenopausal osteoporosis.…”
Section: Introduction Dmentioning
confidence: 99%
“…[6,7] The ethanol extract of flower was screened for antiviral activity, and it was observed that the hyperoside shown significant anti HBV activity. [8] The leaves were tested on bone loss in ovarectomised rats and it was observed that it was able to prevent the ovariectomyinduced femoral osteopenia. [9] The modulatory effect of total flavone of Abelmoschus manihot (TFA) on NMDAactivated current (I NMDA ) was investigated in cultured rat hippocampal neurons using the whole-cell patch-clamp technique.…”
Section: [45]mentioning
confidence: 99%